Evaluating human competencies and their role in improving the quality of health services - a case study at the Public Hospital of Laghouat - Abdelkader Guettaf; zaki farid Abid (Dirassat Journal Economic Issue, 2020)
The purpose of this article is to analyze the conceptual framework for assessing human competencies, to reach the most important methods and tools, to measure the level of competencies, and to study the importance of evaluating human competencies in institutions in general and health institutions in particular, to know how much they contribute to the quality of health services provided. Methods that determine and modify the components of efficiency which are considered the main factors in the excellence and continuity. The study was based on the analytical descriptive approach. The results of the study found that coping with the challenges and changes surrounding health organizations require evaluation of human talent in order to achieve all of the cost, effectiveness, safety, justice and quality health services provided to patients and the community.